(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article analyzes complex approaches to the innovative development of regional industrial sectors based on numerical econometric models. Based on methods such as ARIMA, multivariate regression, panel data model, and innovation indexing, factors affecting industrial growth are identified and optimal strategic directions are proposed. The results of the study analyze the crucial role of scientific and technological potential, digital infrastructure, investment flows, and human capital in the innovative development of industry.